Effectiveness of Cough Etiquette Education with Knowledge and Attitude of Implementing Cough Ethics in Yogyakarta High School Students - Kusbaryanto, -; Haqiqi, Arif Rahma Nur (International Journal of Human and Health Sciences (IJHHS), 2023)
Introduction: Cough etiquette plays a crucial role in preventing the spread of respiratory infections, including respiratory viruses like influenza and COVID-19. High school students are an important target group for education on respiratory hygiene practices, as they are highly susceptible to respiratory infections and can act as potential vectors for transmission. Using proper coughing techniques can keep others at ease and prevent the spreading of sickness. Purpose: This study aims to examine how high school students in Yogyakarta, Indonesia, know about and behave toward coughing. Methods: This quantitative study uses a control group design with a quasi-experimental pre-test and posttest. High school students from Yogyakarta participated in this study as respondents. In the control group, there were 27 samples, whereas there were 29 in the treatment group. A questionnaire was used to collect the data, and the Wilcoxon test was used to analyze it. Findings: The test results on the level of knowledge about cough etiquette in the control group, knowledge about cough etiquette p = 0.791. In the treatment group, knowledge of cough ethics p = 0.032; this is a significant result. In attitudes about cough ethics, the value of p = 0.171 was obtained; this result was insignificant. Originality: The novelty of this research is an increase in knowledge about cough etiquette, which is expected to also increase adherence to cough etiquette. Conclusion: Education about cough etiquette is effective for increasing students’ knowledge about cough etiquette. International Journal of Human and Health Sciences Vol. 07 No. 04 Oct’23 Page: 294-300